Optimalisasi Pendampingan dan Pendaftaran NIB melalui OSS untuk Legalitas UMKM Baratajaya Surabaya - Mayshela, Alfreda Putri; Oktaviya, Ananta; Devi, Azizah Rusita; Salsabilah, Kholida Hanum; Ramadhani, Mirza (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Baratajaya Sub-district in Surabaya has a high potential of MSMEs, especially in culinary fields such as food stalls, catering, and beverage businesses. However, observations showed that most MSME actors did not have a Business Identification Number (NIB) due to a lack of understanding of its importance and the registration procedure. This community service activity aimed to assist MSMEs in obtaining NIB through the OSS system to ensure their business legality. The partners in this program were Baratajaya Sub-district officials, RW 03, and Kader Surabaya Hebat. The methods included observation, socialization about business legality, practical training on NIB registration, and evaluation through participant questionnaires. The results showed an increase in MSME actors’ knowledge and awareness regarding the importance of NIB, as well as their successful registration with the assistance of university students. Most participants expressed satisfaction with the material delivery and practical sessions, which were easy to understand. This activity proved beneficial in supporting MSME business continuity legally and increasing their confidence in running their businesses. The significance of this program is that it becomes an initial step in optimizing MSME legality, which impacts the strengthening of the local economy based on official licensing.